Conducting Polymer‐Based Micro‐ and Nano‐batteries for Biomedical Applications: A Short Review - Singh, Neetika; Kumar, Amit; Riaz, Ufana (ChemistrySelect (Weinheim), 2022)
Current advancements in nanotechnology focus on miniaturization of electronic devices to provide power on demand. The Li+ ion based micro/nano‐batteries are excellent candidates for this purpose. However, the manufacture a single nano‐battery with assured reliable performance is one of the greatest challenges faced in the fabrication of Li+ ion based nano‐batteries. Nanostructured conducting polymers (NCPs) have shown promise in many frontier areas such as biosensors, microelectronics, polymer batteries, actuators, energy conversion etc. The combination of NCPs with inorganic compounds for designing nano‐batteries has been the subject of extensive investigation due to synergistic interaction of NCPs with inorganic compounds that provides remarkable improvement in electrode lifetime, rate capabilities, and voltage as well as mechanical and thermal stability. The present mini review deals with the fabrication of nano‐batteries using polypyrrole (PPy), polyaniline (PANI), and polythiophene (PTh) which could be utilized for various biomedical applications. The design and development of nano‐batteries using NCPs is discussed along with their applications in implantable devices, pace makers, smart sensing devices etc. The advancements in the research of micro and nano batteries using conducting polymers for biomedical instrumentation are of immense technological significance to the scientific communityAdvance manufacturing process and novel evaluation methods are needed for the design of future generations of Li+ ion based batteries.